Application of Nipah Pseudovirus System for Development of Antibody Neutralization Assay - Anna, Shoffiana Noor; Fera Ibrahim (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Nipah virus (NiV) is a type of virus that can make people and many animals very sick. It can cause serious breathing problems and brains welling. Because of how dangerous and deadly it is, the World Health Organization (WHO) sees NiV as a global healthrisk. It needs to be handled in special labs that have the highest safety measures, called Biosafety Level-4 (BSL-4) facilities. Rightnow, there isn't a good vaccine or treatment available for NiV. It could be a health risk for Indonesia since it has been found in nearby countries. Indonesia doesn't have a BSL-4 lab yet. So, we need a way to evaluation NiV vaccine that can be done in a BSL-2 lab. The NiV pseudovirus (PV NiV) has special proteins that help it attach to and enter mammal cells. It is made using a system based on HIV and includes a signal detector. This setup can help create tests to measure how well antibodies work against NiV. It can also be used to monitor infections, check community immunity, develop NiV vaccines, and research new treatments to fight NiV infections.